Development of a portable hardness tester for wood using displacement transducer - Ballarin, Adriano [UNESP]; Assis, Albert [UNESP]; Palma, Hernando Lara [UNESP] (My University, 2014)
Hardness is largely used in material specifications. Specifically for timber, Janka hardness is traditionally performed. More recently, international studies have reported the use of Brinell hardness for timber quality assessment in field conditions, especially due to the lower magnitude of the involved force. Two generation of portable equipment with these purposes were already developed by the Research Group on Forest Products from FCA/UNESP, Brazil for dynamic evaluation of hardness. This paper presents results obtained in the development of the third generation of this equipment, which uses displacement transducer in order to automate the indentation evaluation in wood. Functional tests of the equipment were carried out using seven species of Eucalyptus. Results already obtained revealed strong correlation to Janka hardness and confirmed the potential of the equipment in the classification of wood.
Keywords: Brinell hardness; Displacement transducer; Janka hardness; Portable equipment